Contrasting responses of leaf stomatal characteristics to climate change: a considerable challenge to predict carbon and water cycles. (20th March 2017) - Yan, Weiming; Zhong, Yangquanwei; Shangguan, Zhouping
Abstract: Stomata control the cycling of water and carbon between plants and the atmosphere; however, no consistent conclusions have been drawn regarding the response of stomatal frequency to climate change. Here, we conducted a meta‐analysis of 1854 globally obtained data series to determine the response of stomatal frequency to climate change, which including four plant life forms (over 900 species), at altitudes ranging from 0 to 4500 m and over a time span of more than one hundred thousand years. Stomatal frequency decreased with increasing CO2 concentration and increased with elevated temperature and drought stress; it was also dependent on the species and experimental conditions. The response of stomatal frequency to climate change showed a trade‐off between stomatal control strategies and environmental factors, such as the CO2 concentration, temperature, and soil water availability. Moreover, threshold effects of elevated CO2 and temperature on stomatal frequency were detected, indicating that the response of stomatal density to increasing CO2 concentration will decrease over the next few years. The results also suggested that the stomatal index may be more reliable than stomatal density for determination of the historic CO2 concentration. Our findings indicate that the contrasting responses of stomata to climate change bring a considerable challenge in predicting future water and carbon cycles. Abstract : Stomatal frequency decreased with increasing CO2 concentration and increased with elevated temperature and drought stress, which depended on the species and experimental conditions, and showed a trade‐off between the stomatal control strategies and environmental factors, such as the CO2 concentration, temperature, and soil water availability. Threshold effects of elevated CO2 and temperature on stomatal frequency were detected, indicating that the response of stomatal density to increasing CO2 concentration will decrease over the next few years, and the results also suggested that the stomatal index might be more reliable than stomatal density to predict the historic CO2 concentration. Our findings indicate that the contrasting responses of stomata to climate change bring a considerable challenge in predicting future water and carbon cycles.